Evaluation of Some Aspects of Educational Inputs and Outputs of Community Medicine Departments in Iran Medical Sciences Schools and Universities - Saadat Torabian; Abbas Vosugh Mogadam; Mojtaba Sedaghat Syahkal (Kerman University of Medical Sciences, 2007)
Background: Human health is strongly related to economic political cultural administrative and environmental conditions Therefore Medical sciences are not limited to biomedical sciences but also include social and psychological sciences This viewpoint has led to an outlook named CommunityOriented Medicine After integration of Health System with Medical Education in Iran conditions for Community oriented Medical Education were provided and the departments of Community Medicine in universities with Faculty of Health and departments of Health and Community Medicine in universities without Faculty of Health were established In spite of various attempts there is still no evidence showing the outputs and outcomes of Communityoriented activities in Community Medicine Departments of our universities Objective: This study was performed to determine the statue of Community Medicine Departments of all Medical Sciences schools and Universities of Iran in regard to their facilities and resources Methods: In this descriptive cross sectional study some inputs and outputs of educational and research processes of departments of Community Medicine in all Medical Sciences Universities affiliated to the Ministry of Health Treatment and Medical Education were analyzed Results: Educational facilities and learning aids of first class universities were to some extent adequate but inadequate in the two other classes Community Medicine Departments in all three classes of universities were active in conducting students theses but they were not very active in publishing books and articles and conducting research projects Conclusion: Transition from traditional Medical Education to the communityoriented Medical Education requires shortterm and longterm programs for improving Community Medicine Departments and making them closer to standard goals